„Zaklinać [się] i przysięgać” (Mk 14,71; Mt 26,74) - Pietrzak OP, Jacek (The Biblical Annals, 2019)
The wording describing Peter's third denial: "curse and swear" gave rise to several contradictory interpretations. Some think that it is hendiadys meaning nothing but swearing. Advocates of the transitive sense of the verb ἀναθεματίζω try to guess who is the object of Peter's curse. The dominant view is that Peter curses Jesus. Others think that Peter curses himself or those who accuse him. But formula "curse and swear" appears in the Henochic myth about fallen angels (1 Hen 6:4.5.6). Peter, who denies Jesus, resembles one of the fallen angels, who opposed God's will on Mount Hermon and separated themselves from God. The following pattern, which can be observed in the First Book of Enoch (1-6): the revelation of God, the announcement of the Last Judgment and the fall of those who belong to God appear in the Gospels of Mark and Matthew twice: in Caesarea Philippi (Mark 8:27-38, Matt 16:13-28 ) and in the Caiaphas palace (Mark 14:53-75, Matt 26:57-72). The apocryphal context helps to understand that the curse always touches one who opposes God. Throwing a curse on yourself is confirmed by examples from ancient culture.